Personalized RNA neoantigen vaccines stimulate T cells in pancreatic cancer - Rojas, Luis A.; Sethna, Zachary; Soares, Kevin C.; Olcese, Cristina; Pang, Nan; Patterson, Erin; Lihm, Jayon; Ceglia, Nicholas; Guasp, Pablo; Chu, Alexander; Yu, Rebecca; Chandra, Adrienne Kaya; et al. (Nature (London), 2023)
Pancreatic ductal adenocarcinoma (PDAC) is lethal in 88% of patients 1 , yet harbours mutation-derived T cell neoantigens that are suitable for vaccines 2 , 3 . Here in a phase I trial of adjuvant autogene cevumeran, an individualized neoantigen vaccine based on uridine mRNA–lipoplex nanoparticles, we synthesized mRNA neoantigen vaccines in real time from surgically resected PDAC tumours. After surgery, we sequentially administered atezolizumab (an anti-PD-L1 immunotherapy), autogene cevumeran (a maximum of 20 neoantigens per patient) and a modified version of a four-drug chemotherapy regimen (mFOLFIRINOX, comprising folinic acid, fluorouracil, irinotecan and oxaliplatin). The end points included vaccine-induced neoantigen-specific T cells by high-threshold assays, 18-month recurrence-free survival and oncologic feasibility. We treated 16 patients with atezolizumab and autogene cevumeran, then 15 patients with mFOLFIRINOX. Autogene cevumeran was administered within 3 days of benchmarked times, was tolerable and induced de novo high-magnitude neoantigen-specific T cells in 8 out of 16 patients, with half targeting more than one vaccine neoantigen. Using a new mathematical strategy to track T cell clones (CloneTrack) and functional assays, we found that vaccine-expanded T cells comprised up to 10% of all blood T cells, re-expanded with a vaccine booster and included long-lived polyfunctional neoantigen-specific effector CD8 + T cells. At 18-month median follow-up, patients with vaccine-expanded T cells (responders) had a longer median recurrence-free survival (not reached) compared with patients without vaccine-expanded T cells (non-responders; 13.4 months, P = 0.003). Differences in the immune fitness of the patients did not confound this correlation, as responders and non-responders mounted equivalent immunity to a concurrent unrelated mRNA vaccine against SARS-CoV-2. Thus, adjuvant atezolizumab, autogene cevumeran and mFOLFIRINOX induces substantial T cell activity that may correlate with delayed PDAC recurrence. A phase I clinical trial of an adjuvant personalized mRNA neoantigen vaccine, autogene cevumeran, in patients with pancreatic ductal carcinoma demonstrates that the vaccine can induce T cell activity that may correlate with delayed recurrence of disease.